REVIEW: THE ROLE OF EDUCATIONAL ADMINISTRATION IN IMPROVING THE PROFESSIONALISM OF PAI TEACHERS: Indonesia - Hanifah Utami Rahman; Hinggil Permana (STIT Pringsewu, 2022)
Abstract The purpose of this article is to discuss the role of educational administration in improving teacher professionalism. Educational administration is a set of activities to collect, record, procure, reproduce, send and store various information materials for organizational purposes and consideration for leaders in making appropriate decisions or policy steps. In this case the need for a professional spirit in working with it emphasizes a mental attitude in the form of commitment from a job that becomes his profession. Someone who is a professional will always try to improve and realize the quality of his work. The Contribution of Educational Administration in Improving the Professionalism of PAI Teachers, Educational administration has five contributions in developing the professionalism of PAI teachers, namely: (1) time management, (2) classroom management, (3) stimulates innovation, (4) stimulates technical skills development, and (5) the concept of transforming students. Keywords: Education Administration, PAI Teacher Professionalisme